ANALISIS OPTIMALISASI LOSS TIME ALAT GALI MUAT UNTUK MENCAPAI TARGET PRODUKSI OVERBURDEN DI PIT TIMUR PT ALLIED INDO COAL JAYA KOTA SAWAHLUNTO, SUMATERA BARAT. - Arif Nandi Rivai; Adree Octova (Departemen Teknik Pertambangan FT UNP, 2021)
Overburden stripping is an activity that affects mining activities, the more optimal the overburden stripping activity, the coal mining activities will be in accordance with the targets set by the company. PT Allied Indo Coal Jaya in the East Pit has set an overburden production target in November 2020 of 110,000 BCM/month for 2 mining fleets. However, based on overburden production data, the production achieved was 86,126.20 bcm, only 78.30% of the target achieved. The available working time for each mining fleet is 268 hours, but the time for the Unit 018 fleet is 216.74 hours and the 021 fleet is 220.08 hours. There is losstime which is a factor in not achieving the overburden production target. The losstime problem consists of Idle Time and Delay Time. Based on the problem, action is taken on losstime for digging equipment with optimization of overburden production time. Analysis of the data used is multiple linear regression analysis using the least squared method. To get the optimal time simulation of loss time in meeting production targets in the East Pit of PT Allied Indo Coal Jaya. The data used are loss time data (idle time and delay time) and aqua production data. Optimal losstime that can be applied to the fleet Unit 018 with an idle time of 0.41 hours/day and a delay time of 0.05 hours/day and the fleet Unit 021 with an idle time of 0.57 hours/day and a delay time of 0.08 hours/day. Where the overburden production achieved from these two fleets is 114,020.57 bcm/month. Keywords : Production, Losstime, least squared